Sex-specific behavioral outcomes of early-life adversity and emerging microglia-dependent mechanisms - Garvin, Madison M.; Bolton, Jessica L. (Frontiers in Behavioral Neuroscience, 2022)
Early-life adversity (ELA) is known to alter brain circuit maturation as well as increase vulnerability to cognitive and emotional disorders. However, the importance of examining sex as a biological variable when researching the effects of ELA has not been considered until recently. This perspective discusses the sex-specific behavioral outcomes of ELA in both humans and animal models, then proposes microglia-mediated mechanisms as a potential underlying cause. Recent work in rodent models suggests that ELA provokes cognitive deficits, anhedonia, and alcohol abuse primarily in males, whereas females exhibit greater risk-taking and opioid addiction-related behaviors. In addition, emerging evidence identifies microglia as a key target of ELA. For example, we have recently shown that ELA inhibits microglial synapse engulfment and process dynamics in male mice, leading to an increase in excitatory synapse number onto corticotrophin-releasing hormone (CRH)-expressing neurons in the paraventricular nucleus of the hypothalamus (PVN) and aberrant stress responses later in life. However, ELA-induced synaptic rewiring of neural circuits differs in females during development, resulting in divergent behavioral outcomes. Thus, examining the role of microglia in the sex-specific mechanisms underlying ELA-induced neuropsychiatric disorders is an important topic for future research.